2010
DOI: 10.1038/eye.2010.190
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic injuries in British Armed Forces in Iraq and Afghanistan

Abstract: Outcomes assessed by final best-corrected visual acuity (VA; few patients lost to follow-up), rates of endophthalmitis, and proliferative vitreoretinopathy (PVR). Results There were 630 cases of major trauma, 63 sustained eye injuries (10%), and 48 sustained significant eye injuries. There were 21 open-globe injuries: 9 ruptures and perforating injuries, of which 7 were enucleated/eviscerated; 11 intraocular foreign body (IOFB) injuries, of which 1 was eviscerated. Primary repair was combined with posterior se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 17 publications
4
58
1
Order By: Relevance
“…However, a previous series reported no cases of endophthalmitis following ocular trauma due to explosive material. [19][20][21][22] In most of the patients, signs of burns on the eyelids and ocular surface and in the vitreous gel suggested that injuries from hot, projectile particles may be associated with endophthalmitis less frequently than are other penetrating ocular injuries.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous series reported no cases of endophthalmitis following ocular trauma due to explosive material. [19][20][21][22] In most of the patients, signs of burns on the eyelids and ocular surface and in the vitreous gel suggested that injuries from hot, projectile particles may be associated with endophthalmitis less frequently than are other penetrating ocular injuries.…”
Section: Discussionmentioning
confidence: 99%
“…2 The decision to defer surgery to normal working hours is supported by recent research on delayed primary repair in patients injured in military conflict situations, where low complication rates were observed with this approach. 4 The belief that delayed surgery would not significantly affect the outcome for the patient was a quoted reason for deferral for 183 responding consultants in our survey.…”
Section: Discussionmentioning
confidence: 99%
“…1 To date, there are limited data on the optimal management of these cases as they are rare and varied; recent work on the management of open-globe injuries in military situations with a mean time to primary repair of 1.9 days had final visual acuities which correlated with the Ocular Trauma Score. 4,5 Better final outcomes were described for perforating globe injuries and intraocular foreign bodies that had delayed secondary repair or removal of foreign body, but these patients had undergone primary repair 'within hours'. 6,7 It is clear from our data that certain situations, such as pediatric trauma and endophthalmitis, may be treated as exceptional cases, and these will invariably make up a significant minority of out of hours presentations.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate visualization, inability to induce PVD and hemorrhage may be less of a problem in delayed surgery. Some studies have shown that delayed removal of IOFBs is not associated with poorer visual or anatomical outcomes 27,28 . As it has been shown that prophylactic injection of intravitreal antibiotics reduces the risk of endophthalmitis, if a delayed surgery is planned, intravitreal injection of antibiotics is indicated during primary repair 34 .…”
Section: Preoperative Evaluation: Preoperative Evaluation Of Iofbsmentioning
confidence: 99%
“…War injuries also have a high probability of IOFBs. [26][27][28] Sometimes foreign bodies are entered into the eye by a larger object impacting the eye such as cilia that enter the eye through penetrating traumas by objects like stone or wood.…”
Section: Intraocular Foreign Bodies (Iofbs)mentioning
confidence: 99%